Keanekaragaman dan Biomassa Ikan Karang serta Keterkaitannya dengan Tutupan Karang Hidup di Perairan Manggis, Kabupaten Karangasem, Bali - Putra, I Made Raditya; Dirgayusa, I Gusti Ngurah Putra; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 5 No 2 (2019), 2018)
The existence of coral reef fish is closely related to the availability of coral reef resource as a habitat. Coral reef fish is a biota that has a fascination with a variety of color patterns and fascinating. Differences in coral cover conditions will affect the abundance of coral reef fish, especially those with strong linkages to living corals. This research was conducted in June - August 2017 by using line intercept transect (LIT) method for coral cover percentage and visual census method for biodiversity and biomass of coral reef fish with 3 research stations in Manggis waters, Karangasem. From the research results, it shows that the diversity index ranged between 2.54 - 2.70 which means the diversity of coral reef fish in the medium category and the stability of the community is in the medium. Furthermore, total biomass of coral reef fish ranged between 186,17 - 1692,08 kg / ha. The results stated that the percentage of live coral cover in Manggis waters ranged from 3.83% to 12.44% which means that live coral cover is categorized as bad. A very strong positive correlation between living coral conditions and coral reef fish biomass was 92.42%. Meanwhile, the relationship between living coral conditions and the diversity of coral reef fish had a strong positive correlation of 65.4%. The diversity of coral reef fish in waters is not only caused by live coral cover; however, it is caused by coral reef ecosystems that are associated in the bottom of the waters.